Prognostic factors for development of acute respiratory distress syndrome following traumatic injury: a systematic review and meta-analysis. Issue 4 (14th April 2022) - Tran, Alexandre; Fernando, Shannon M.; Brochard, Laurent J.; Fan, Eddy; Inaba, Kenji; Ferguson, Niall D.; Calfee, Carolyn S.; Burns, Karen E.A.; Brodie, Daniel; McCredie, Victoria A.; Kim, Dennis Y.; Kyeremanteng, Kwadwo; et al.
Background: Our purpose was to summarise the prognostic associations between various clinical risk factors and development of acute respiratory distress syndrome (ARDS) following traumatic injury. Methods: We conducted this review in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and CHARMS (Critical Appraisal and Data Extraction for Systematic Reviews of Prediction Modeling Studies) guidelines. We searched six databases from inception through December 2020. We included English language studies describing the clinical risk factors associated with development of post-traumatic ARDS, as defined by either the American–European Consensus Conference or Berlin definition. We pooled adjusted odds ratios for prognostic factors using the random effects method. We assessed risk of bias using the QUIPS (Quality in Prognosis Studies) tool and certainty of findings using GRADE (Grading of Recommendations Assessment, Development and Evaluation) methodology. Results: We included 39 studies involving 5 350 927 patients. We identified the amount of crystalloid resuscitation as a potentially modifiable prognostic factor associated with development of post-traumatic ARDS (adjusted OR 1.19, 95% CI 1.15–1.24 for each additional litre of crystalloid administered within the first 6 h after injury; high certainty). Non-modifiable prognostic factors with a moderate or high certainty of association with post-traumatic ARDS included increasing age, non-Hispanic White race, blunt mechanism of injury, presence of head injury, pulmonary contusion or rib fracture and increasing chest injury severity. Conclusions: We identified one important modifiable factor, the amount of crystalloid resuscitation within the first 24 h of injury, and several non-modifiable factors associated with development of post-traumatic ARDS. This information should support the judicious use of crystalloid resuscitation in trauma patients and may inform development of risk stratification tools. This systematic review identifies one important modifiable factor, the amount of crystalloid resuscitation within the first 24 h of injury, and several non-modifiable factors associated with development of post-traumatic ARDS https://bit.ly/3klhshF